EWOLUCJA PRAWA OCHRONY GRANIC POLSKI W XX-XXI WIEKU - Lech Grochowski (Zeszyty Prawnicze)
THE EVOLUTION OF POLISH BORDER PROTECTION LAW IN 20TH AND 21ST CENTURY Summary The borderland, i.e. the area of land close to the border between two countries, is always a piece of land of exceptional importance. Depending on the current situation the authorities consider it as a more or less effective barrier which protects the state against any kind of economic, political or military threat. The crucial issue in the process of delineating the area is determining the depth of the zone. Protection of sovereignty of any state involves high concentration of various public safety and military defence installations in the borderland. As we move towards the interior the installations in question become more and more scarce. Thus, the borderland is divided into sub-zones which division is reflected in different border crossing regulations for each individual sub-zone.